(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
There has been a rise in the incidence of sudden death among individuals in middle age. Predominantly, cardiovascular diseases have seen to be the most leading cause behind such deaths. Despite being a relatively uncommon presentation, cardiac tamponade presents as one of the rare yet fatal complications. This condition manifests when the pericardial cavity becomes filled with either blood or blood clots, compromising the heart’s normal contractile function. Typically, patients experiencing cardiac tamponade are often reported to have succumbed to sudden death, with history of chest pain. The definitive diagnosis of cardiac tamponade usually occurs during post-mortem examinations during Autopsy. We consider the case of a 45-year-old man who was found unconscious at his residence and was pronounced dead upon arrival at the hospital. Subsequent autopsy findings unveiled the presence of both blood and blood clots within the pericardial cavity, in conjunction with a rupture in the left ventricle and occlusion of the right coronary artery. Histopathological examination further confirmed the root cause of this fatal event as an acute myocardial infarction.